If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 = 3u + 6(u + -3) Reorder the terms: 36 = 3u + 6(-3 + u) 36 = 3u + (-3 * 6 + u * 6) 36 = 3u + (-18 + 6u) Reorder the terms: 36 = -18 + 3u + 6u Combine like terms: 3u + 6u = 9u 36 = -18 + 9u Solving 36 = -18 + 9u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-9u' to each side of the equation. 36 + -9u = -18 + 9u + -9u Combine like terms: 9u + -9u = 0 36 + -9u = -18 + 0 36 + -9u = -18 Add '-36' to each side of the equation. 36 + -36 + -9u = -18 + -36 Combine like terms: 36 + -36 = 0 0 + -9u = -18 + -36 -9u = -18 + -36 Combine like terms: -18 + -36 = -54 -9u = -54 Divide each side by '-9'. u = 6 Simplifying u = 6
| -9-x=-6(2x+7) | | -5x+4x+20-10x= | | -11=7y+8(y+8) | | -22+6r=-8r-6(1-r) | | 2a+a=-21 | | (750-x)-600-y=3x-y | | 120.08=2808.97(r) | | (2y-80)=(y+9) | | 7(d-3)+6= | | (8x+12)=(10x-24) | | 3x-4+4x+8+x=180 | | (x+30)=(2x) | | 7x-4x+x-4+3x= | | 6.5x-5+x-1.2= | | 4b-6-9b-8= | | 682/d=21 | | (3x-15)=(2x+25) | | -5=5x+5y | | 50(t)=-16t^2+50o | | 50(t)=-16t^2+ho | | h(t)=-16t^2+ho | | 2(-8)-21(-8)-7= | | 25-15(-8)= | | 45=9/2h | | 25-15(8)= | | 45=1/2h(9) | | 2(8)-21(8)-7= | | ×=2/3 | | 9/7(M-19) | | -2x+3=5x-2 | | 7x^9/8-35=0 | | -7(3)+13= |